Teaching English at primary school under Merdeka curriculum: Students' voices - Falah, Irfan Fajrul; Apsari, Yanuarti; Kusumah, Rita (The Proceedings of English Language Teaching, Literature, and Translation (ELTLT), 2023)
The transformation of the education curriculum is inevitable since the quality of teaching and learning should be improved. In Indonesia for instance, it has experienced more than 10 changes since the independence up to now where the Merdeka curriculum is implemented. As a part of the curriculum, the status of English at the primary level remains the same. It is an elective subject that can be taught based on school readiness which is no different compared to the previous curriculum (K-13 Curriculum). However, given the new look of the curriculum that emphasizes students' interest and needs in learning, it is worth identifying how students at primary schools perceive learning. In addition, the students' voices particularly in teaching English have not been given priority. The participants of the study were 147 primary school students (N-147, 80 males and 67 females) who learn English in the first and fourth grades. In this study, the researchers used several techniques for collecting data including a questionnaire that cover four aspects; students’ interests; methods; media, and students’ comprehension activities. In addition, the researchers use also focus group discussions that were held on the site. The results show that several issues are still there to be solved sooner rather than later. Therefore, the quality of teaching English at the primary level could be better in the future.